Banking Industry Consolidation in Nigeria: Regulatory Challenges and Efficiency Issues. - Ugwunze, Ifeoma (2007)
The Banking Industry has embarked on a trend toward consolidation that is expected to continue into the future. There are mergers that have transformed regional banks into national banking powerhouses with a significant impact on shareholders, customers and communities involved. Performance evaluation of the banking sector in Nigeria has assumed primal importance due to intense competition, greater customer demands and banking reforms. The first phase of the reforms constitute strengthening and consolidating the banking system which is designed to ensure a diversified, strong and reliable banking sector which will ensure the safety of depositors money and play active developmental roles in the Nigerian economy. The Nigerian Banking sector remains very marginal relative to its potentials and in comparison to other countries even in Africa.Also,the inability of the banking system to voluntarily embark on consolidation in line with the global trend has actually necessitated the need to consider the adoption of appropriate legal and supervisory frameworks as well as a comprehensive incentive package to facilitate mergers and acquisition (M&A) in the sector as a crisis resolution option and to promote the soundness, stability and enhanced efficiency of the system.